169k views
0 votes
How do you solve the problem and what is the answer?

-2 = g -9


2 Answers

3 votes

Answer:

g=7

Step-by-step explanation: You have to first get the variable alone. So, you would add 9 since it is on the side of the variable, and you add because you do the opposite of what is being done. You would do this on both sides, therefore the answer is 7.

User Alex Ketay
by
5.9k points
4 votes

Answer:

Hey Dude ok so it's g = 7 Have a nice day!

Step-by-step explanation:Simplifying

-2 = g + -9

Reorder the terms:

-2 = -9 + g

Solving

-2 = -9 + g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-1g' to each side of the equation.

-2 + -1g = -9 + g + -1g

Combine like terms: g + -1g = 0

-2 + -1g = -9 + 0

-2 + -1g = -9

Add '2' to each side of the equation.

-2 + 2 + -1g = -9 + 2

Combine like terms: -2 + 2 = 0

0 + -1g = -9 + 2

-1g = -9 + 2

Combine like terms: -9 + 2 = -7

-1g = -7

Divide each side by '-1'.

g = 7

Simplifying

g = 7

User GivenPie
by
4.8k points